Anticholinergic drugs and negative outcomes in the older population: from biological plausibility to clinical evidence - Collamati, Agnese; Martone, Anna Maria; Poscia, Andrea; Brandi, Vincenzo; Celi, Michela; Marzetti, Emanuele; Cherubini, Antonio; Landi, Francesco (Aging clinical and experimental research, 2016)
The use of medication with anticholinergic properties is widespread among older subjects. Many drugs of common use such as antispasmodics, bronchodilators, antiarrhythmics, antihistamines, anti-hypertensive drugs, antiparkinson agents, skeletal muscle relaxants, and psychotropic drugs have been demonstrated to have an anticholinergic activity. The most frequent adverse effects are dry mouth, nausea, vomiting, constipation, abdominal pain, urinary retention, blurred vision, tachycardia and neurologic impairment such as confusion, agitation and coma. A growing evidence from experimental studies and clinical observations suggests that drugs with anticholinergic properties can cause physical and mental impairment in the elderly population. However, the morbidity and management issues associated with unwanted anticholinergic activity are underestimated and frequently overlooked. Moreover, their possible relation with specific negative outcome in the elderly population is still not firmly established. The aim of the present review was to evaluate the relationship between the use of drugs with anticholinergic activity and negative outcomes in older persons. We searched PubMed and Cochrane combining the search terms “anticholinergic”, “delirium”, “cognitive impairment”, “falls”, “mortality” and “discontinuation”. Medicines with anticholinergic properties may increase the risks of functional and cognitive decline, morbidity, institutionalization and mortality in older people. However, such evidences are still not conclusive probably due to possible confounding factors. In particular, more studies are needed to investigate the effects of discontinuation of drug with anticholinergic properties. Overall, minimizing anticholinergic burden should always be encouraged in clinical practice to improve short-term memory, confusion and delirium, quality of life and daily functioning.